1979
DOI: 10.1063/1.555591
|View full text |Cite
|
Sign up to set email alerts
|

Energy levels of titanium, Ti I through Ti XXII

Abstract: The energy levels of the titanium atom in all of its stages of ionization, as derived from the analyses of atomic spectra. have been critically compiled. In cases where only line classifications are reported in the literature, level values have been derived. Term designations, experimental g.values, and ionization energies are included. Calculated percentages of the two leading components of the eigenvectors of the levels are given.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
0

Year Published

1982
1982
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(23 citation statements)
references
References 25 publications
2
21
0
Order By: Relevance
“…Some low terms are not tabulated by Corliss and Sugar (1979). We could not find 3d 3 (b 2 F)4s 3 F, expected at ca.…”
Section: We Attempted To Gain Some Insight Into the Location Of Tjj Fmentioning
confidence: 80%
“…Some low terms are not tabulated by Corliss and Sugar (1979). We could not find 3d 3 (b 2 F)4s 3 F, expected at ca.…”
Section: We Attempted To Gain Some Insight Into the Location Of Tjj Fmentioning
confidence: 80%
“…It indicates that the TiX radicals are well described as Ti + X À in the lower energy region. It is suggested that this picture may be extended to the 4 C state of TiX, which is correlated with the lowest 4 G state of the Ti + ion located $30 000 cm À1 above the 4 F ground state and belonging to the 3d 2 4p configuration [16]. The ionic picture of Ti + X À may give a useful insight for understanding the 4 C state of TiX.…”
Section: Discussionmentioning
confidence: 95%
“…The available theoretical n=3 level schemes [4,[13][14][15], though similar to each other and to extrapolated experimental data, need to be adjusted to match the experimental term values [17]. In order to facilitate comparisons of theoretically predicted level schemes and experimental spectra, spectra based on theoretical data were simulated.…”
Section: Discussionmentioning
confidence: 99%
“…transitions) all lie in the wavelength interval 28 nm_< 2 <_ 60 nm where indeed most of the medium intensity or even strong lines which could not be identified previously are to be found. Where several line identifications were possible, the level assignment approximating the multiplet splittings of Bureeva [17,18] Because of a certain degree of arbitrariness in several identifications a few comments will be given:…”
Section: Discussionmentioning
confidence: 99%